An Unusual Presentation of Acute Pericarditis in a Young COVID19 Patient: a Case Report - Muhammad Hazwan Nasarudin; Alif Adlan Mohd Thabit; Suraya Hanim (Asian Journal of Medicine & Health Sciences, 2022)
COVID-19 is a worldwide pandemic, even in the year 2022. Extrapulmonary manifestations are rare, especially cardiovascular involvement. Our case report described a teenage boy with positive COVID-19 who presented with symptoms suggestive of acute pericarditis. An echocardiogram revealed mild loculated pericardial effusion. He was treated with oral colchicine 0.5mg BD for two weeks, and repeated ECG showed resolution of the ECG changes. He remained asymptomatic throughout the admission and during follow-up. More studies are needed to understand the cardiac involvement in COVID-19 to provide better treatment in the future.